Bacteria as Self-Healing Agent in Mortar Cracks - Ananto Nugroho; Iman Satyarno; Subyakto Subyakto (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
This study was aimed at finding the possibility to apply Bacillus subtilis integrated into mortar matrix to act as a self-healing agent to seal cracks. Bacterial spores at concentrations of 104, 105, and 106 cells/ml were directly added into pulverized fly ash as medium to protect bacteria in high alkaline conditions. The results show that the addition of Bacillus subtilis spores into the mortar mixture enhanced the compressive strength, especially at a cell concentration of 105 cells/ml. The bacterial mortar had a small ability to recover the stiffness of the mortar, amounting to 34.85% of its original stiffness. The effectiveness of crack sealant and resistance to water flow were limited to a maximum crack width size of 0.22 mm. Physical observation showed that the bacterial mortar is characterized by calcite precipitation as a product of ureolytic bacteria. The quantity and distribution of calcite precipitate depended on the precipitation weight, gravity direction and oxygen availability. Meanwhile, chemical analysis using XRD and EDX showed that the bacterial mortar had a better crystallinity.